ANALISIS PIUTANG TAK TERTAGIH BERDASARKAN UMUR PIUTANG PADA PT. AIR MANADO - Kiay Demak, Yulindasari; Tinangon, Jantje J.; Mawikere, Lidia (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Receivables Represents a number of bills that will be received by a company generally in the form of cash from another parties, as a result of the sale of goods and services on credit. Receivables are often faced with the risk of uncollectibility and sometimes these invoices cannot be avoided and can result in uncollectible receivables / receivables. This research was carried out on PT. Air Manado. The purpose of this study is to analyze the recording of uncollectible receivables on PT. Air Manado, in order to know how to record uncollectible accounts. This study uses descriptive research methods, and data collection techniques used are interview and documentation techniques. The results of this study indicate that the recording of uncollectible accounts at PT. Air Manado it is good because it is in accordance with the provisions and agreement with the investor has also been in accordance with the theory of age method of accounts receivable.Keywords : uncollectible receivables, age of account receivables